PENILAIAN MASYARAKAT TERHADAP KESIAPAN PENERAPAN KONSEP KAWASAN TRANSIT ORIENTED DEVELOPMENT (TOD) DI STASIUN PONDOK CINA, DEPOK, JAWA BARAT - Rizky, Dhio Muhammad; Arris Maulana; Daryati (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2022)
Implementation TOD in the development stage in order to aspects of benefit for community, such as implementation TOD for Pondok Cina Station with Mahata Margonda. Seeing that the condition is still in construction stage, it can changes to environment, this study aims to determine the community's assessment of the readiness to implement TOD. The research distributing questionnaires whose respondents were train users, the total population was 1500, using the Slovin formula, the total sample was 94. The method used is survey using a quantitative. Data analysis in this study uses percentage scale, determine category of assessment and for each assessment indicator. The preparation of the questionnaire is based on assessment indicators which the principles of TOD, 1. Diversity & Destination, Density, Distance&Design, Demand Management. Based on the 5 categories of assessment, the public acceptance of implementation TOD is in the